β2-Adrenergic Receptor Enhances the Alternatively Activated Macrophages and Promotes Biliary Injuries Caused by Helminth Infection - Koda, Stephane; Zhang, Beibei; Zhou, Qian-Yang; Xu, Na; Li, Jing; Liu, Ji-Xin; Liu, Man; Lv, Zi-Yan; Wang, Jian-Ling; Shi, Yanbiao; Gao, Sijia; Yu, Qian; et al. (Frontiers in Immunology, 2021)
The autonomic nervous system has been studied for its involvement in the control of macrophages; however, the mechanisms underlying the interaction between the adrenergic receptors and alternatively activated macrophages (M2) remain obscure. Using FVB wild-type and beta 2 adrenergic receptors knockout, we found that β2-AR deficiency alleviates hepatobiliary damage in mice infected with C. sinensis. Moreover, β2-AR deficient mice decrease the activation and infiltration of M2 macrophages and decrease the production of type 2 cytokines, which are associated with a significant decrease in liver fibrosis in infected mice. Our in vitro results on bone marrow-derived revealed that M2 macrophages from Adrb2-/- mice significantly decrease M2 markers and the phosphorylation of ERK/mTORC1 compared to that observed in M2 macrophages from Adrb2+/+. This study provides a better understanding of the mechanisms by which the β2-AR enhances type 2 immune response through the ERK/mTORC1 signaling pathway in macrophages and their role in liver fibrosis.